Perspektif Female Gaze Dalam Karya Seniman Modern Indonesia, Emiria Soenassa - Apriyulia, Apriyulia; Adriati, Ira; Damayanti, Nuning Yanti (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2024)
The search for national identity in the development of modern Indonesian art has given birth to many artists with their characteristics. Emiria Soenassa, one of the pioneering female artists, plays a vital role in creating a vision of diversity that unites modern Indonesia today. Soenassa's works reflect her complex life experiences through the perspective of the female gaze, making her an important example of contemporary Indonesian art. This research explores how Soenassa's works position their subjects with a female gaze approach and how this contributes to gender struggles in the fine arts. The methodology used is a qualitative approach with descriptive analysis through archival research. The work was analyzed by applying the female gaze theory by Laura Mulvey and the Ways of Seeing concept by John Berger to understand women's perspectives and feminist art in the Indonesian context. This research will provide new insight into the contribution of female artists to the development of modern art in Indonesia.